Фазові рівноваги в системі ZnO–Sb2O5 - Милян, П. М.; Семрад, О. О.; Сідей, В. І; Соломон, А.М.; Milyan, P. M.; Semrad, E. E.; Sidey, V. I.; Solomon, A. M. (Волин. нац. ун-т ім. Лесі Українки, 2008)
Методом твердофазної реакції одержано сплави системи ZnO−Sb2O5. 3 а результатами рентгенофазового та хімічного аналізів проведено їх ідентифікацію. Доведено існування двох тернарних сполук ZnSb2O6 та Zn7Sb2O12. Вивчено деякі фізико-хімічні властивості та побудовано структурні моделі для цих сполук. The series of samples of the ZnO–Sb2O5 quasibinary system have been synthesized by solid-state reactions and characterized by using X-ray powder diffraction techniques (XRD) and chemical analysis. Two intermediate ternary phases, the compounds ZnSb2O6 and Zn7Sb2O12, have been found in the system ZnO–Sb2O5; and the structural models have been built for these compounds.
Phase Equilibria in the ZnO−Sb2O5 System
Keywords: рентгенофазовий аналіз; тернарна сполука; властивості; X-ray phase analysis; ternary compound; properties